How transformational leadership influences employees' job-related outcomes through public service motivation: Does power distance orientation matter? - Bui Nhat Vuong; Ha Nam Khanh Giao; Doan Van Hung (Cogent Business & Management, 2023)
The goal of this research is to examine the influence of transformational leadership (TL) on employees' job-related outcomes, noting the mediating roles of public service motivation (PSM) as well as the moderating effect of power distance orientation (PDO). Surveys were collected from 605 civil servants currently working in local governments in Vietnam and the researcher used the partial least squares structural equation modeling (PLS-SEM) technique with SmartPLS 3.0 software to test hypotheses. The findings showed that there was a positive influence of transformational leadership on employees' work outcomes; this relationship was mediated partially through public service motivation. Also, the finding revealed the moderating effects of power distance orientation on the effect of perceived transformational leadership on public service motivation, job satisfaction, and job performance. Civil servants with high power distance orientation tended to dampen the positive relationship between transformational leadership and public service motivation which led to decreased job satisfaction and job performance. Based on the findings, it is recommended that managers or leaders in Vietnamese local governments should apply transformational leadership in practice to improve the level of employee work outcomes. Finally, this study broadens new knowledge to the existing literature on transformational leadership and job-related outcomes by proposing an alternative model of how this relationship exists. Besides, the findings showed that although transformational leaders can lead to good behavioral outcomes, high power distance orientation could mitigate this benefit.
Keywords: 650; civil servants; employees’ job-related outcomes; power distance orientation; public service motivation; transformational leadership